Family Gathering as a Scientific Approach to Parenting Education: Enhancing Parenting Styles and Social Behavior in Children with Intellectual Disabilities at SLB Lentera Bunda, Solok - Titin Sumarni; Damri; Nurhastuti; Rahmahtrisilvia (Postgraduate, University of Mataram, 2025)
This study examines the effectiveness of family gathering as a scientific approach to parenting education in improving parenting styles and social behavior among children with intellectual disabilities at SLB Lentera Bunda, Solok. Using a mixed-method design with a one-group pretest-posttest model, the research involved 10 children and 9 parents who participated in two structured family gathering sessions integrating recreational and educational elements. Quantitative data were collected through observation checklists measuring 21 indicators of social behavior, while qualitative data were gathered via in-depth interviews and field documentation. Results showed a significant increase in children’s average social behavior score from 12.4 (pretest) to 14.3 (posttest), confirmed by a paired t-test (p = 0.001). Thematic analysis revealed a shift in parenting styles from authoritarian to democratic, with parents reporting improved communication, emotional regulation, and collaborative decision-making. The activity fostered a supportive environment for experiential learning, strengthened parent-child interaction, and enhanced social skills in children. Findings confirm that family gathering, when designed educationally, functions as a valid psychosocial intervention. It is recommended as a structured program in special education settings to promote holistic development through family-school collaboration.